High resolution FTIR study of the ν5, ν6, and ν9 fundamental bands of CH2D37Cl. (August 2021) - Stoppa, Paolo; Pietropolli Charmet, Andrea; De Lorenzi, Alessandra; Tamassia, Filippo; Melosso, Mattia; Cané, Elisabetta; Dore, Luca; Puzzarini, Cristina
Highlights: Recording the first high-resolution infrared spectra of CH2 D 37 Cl. A study of the lowest fundamentals ν5, ν6 and ν9 has been performed. The c -type Coriolis resonance between the v 5  = 1 and v 6  = 1 states is considered. A set of spectroscopic constants for the excited vibrational states is determined. The spectral simulations well reproduce the experimental data. Abstract: The first high-resolution infrared spectra of CH2 D 37 Cl have been investigated in the region 650–1100 cm −1 where the lowest fundamental bands ν5 (826.2626 cm −1 ), ν6 (708.4307 cm −1 ), and ν9 (986.3405 cm −1 ) occur. These vibrations perturb each other by different weak interactions and the v 5  = 1 and v 6  = 1 states were treated according to a model which accounts for a c -type Coriolis resonance. The spectral analysis resulted in the identification of 1664, 2550 and 2657 ro-vibrational transitions for ν5, ν6, and ν9 bands respectively, and to the determination of accurate spectroscopic parameters by using the Watson's A -reduction Hamiltonian in the I r representation. The simulations of the ro-vibrational structure of the ν5, ν6, and ν9 bands performed in different spectral regions adequately reproduce the experimental data.